A Comparative Approach for the C-H Bond Oxidation of Arylalkanes in Water Using ASS-M(acac)n - Sodhi, Ravinderpal K.; Paul, Satya (Current Organocatalysis, 2017)
Background: The biopolymer-containing hybrid composite materials of silica have drawn attention owing to their promising properties and biocompatibility with living matter. Silica component in such hybrids is responsible for the properties like temperature and mechanical resistance, porosity, while the biopolymer offers extra functionality and framework to the hybrid matrices. This work is devoted to selective C-H bond oxidation and heterogeneous catalysis, which are important from the viewpoint of green and sustainable chemistry. Methods: A series of different metal acetylacetonates covalently anchored onto amine functionalized silica/starch composite [ASS-M(acac)n] were developed via surface functionalization with 3-aminopropyl- silica/starch composite, followed by schiff condensation of the surface -NH2 with M(acac)n [Co(acac)2, Cu(acac)2, Pd(acac)2, Ru(acac)3, Mn(acac)3, Co(acac)3]. Results: The catalytic activity of the synthesized catalysts was examined for the C-H bond oxidation of arylalkanes. Co(acac)2 supported onto amine functionalized silica/starch [ASS-Co(acac)2] was found to be efficient catalyst for the C-H bond oxidation of arylalkanes with t-BuOOH in water. Various alkyl benzenes including toluenes, ethylbenzene and alkylhydrocarbons were oxidized efficiently to their corresponding products. The catalyst was characterized by various techniques such as FT-IR, SEM, TEM, TGA and AAS analysis. Conclusion: A series of different organic/inorganic composite catalysts have been synthesized by covalently immobilizing metal acetylacetonate complexes over amine functionalized silica/starch composites. Easy preparation/heterogeneous nature of catalyst, higher yields, aqueous medium and versatility towards various substrates make this method a facile tool for desired oxidations.
Keywords: C-H bond oxidation